Parasitoid Hymenopterans Associated With Erionota Thrax (Lepidoptera: Hesperiidae) In Kota Samarahan - Ahmad Zulwafi, Mohd Zaki (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The association of Erionota thrax with parasitoid hyrnenopterans was studied at banana plantation in Kata Samarahan. The aim of the study was to examine and identified the species parasitic hymenopterans associated with E. thrax. The samples were collected from banana plantation in Kota Samarahan and be reared in laboratory. The emerged parasitoid wasps were collected using aspirators and then transferred to 70% ethanol before they were dried and mounted as specimens. Four species of parasitoid hyrnenopterans were identified, namely Casinaria sp., Cotesia sp., Eurytoma sp. and Brachymeria sp. There were quite large in number of individuals of parasitoid hymenopterans emerged from the E. thrax which 115 individuals, 64 individuals from larvae and 51 individuals are from pupae. Cotesia sp. was family Braconidae and Casinaria sp. was family Ichneumonidae and these two species emerged from the larva. Another two species Brachymeria sp. from Family Chalcididae and Eurytoma sp. from Eurytomidae were emerged from pupae of the E. thrax. For additional information about the association, studying about the association could be improvised by more focusing on the distribution of parasitoid hyrnenopterans in Kota Samarahan and also its behavioral.